ANALISIS FAKTOR KESIAPAN PEMERINTAH DALAM MENERAPKAN AKUNTANSI PEMERINTAH BERBASIS AKRUAL (Studi Kasus Pada SKPD Kabupaten Rokan Hilir) - Norfaliza -; Taufeni Taufik; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of the human resources, organizational commitment, support device on the readiness of the implementation of the accrual-based government accounting standards. The population in this study is the Head of finance and financial staff who work on theentire SKPD Rokan Hilir. The sampling technique using purposive sampling method. The number of respondents in this study were 58 respondents. The data of this study uses primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. Adjusted R-square test results obtained at 0.753 or 75.3%, this means that the contribution of indepen den variables influence the dependent variable was 75.3%. While the remaining 24.7% can be explained by other factors that are not disclosed in this study, such as communication, skills, behaviors and others.Keywords: Accrual-based, government, accounting, human resources, and commitment.